Sleep Pattern and Problems in Young Children Visiting Outpatient Department of a Tertiary Level Hospital in Kathmandu, Nepal. (3rd December 2020) - Pandey, Shrijana; Bhattarai, Shristi; Bhatta, Anwesh
Abstract : Background . Sleep is an important parameter of a child's growth and development. The pattern and duration of sleep varies with age. Sleep problems are a common occurrence during childhood days, and these problems that establish in childhood are presumed to continue later in life. Many times, parental concerns regarding their child's sleep problems like difficulty in putting to sleep, frequent night time awakening, and waking up early are overlooked during their visits to the hospital. Objective . The aim of this study was to find out the sleep patterns and problems of children aged six to thirty-six months. Methodology . A cross-sectional study was conducted at the pediatric outpatient department of Kathmandu Medical College Teaching Hospital from October, 2019 till March, 2020. Two hundred and forty-nine respondents were chosen purposively and were given questionnaires to be filled out. Research instrument was a standard, Nepali version of a structured questionnaire called Brief Infant Sleep Questionnaire (BISQ) which contained questions related to sleep parameters and sleep problems existing among young children of 6-36 months. Mean, standard deviation, frequencies, and Kruskal Wallis test were used for statistical analysis. Results . The mean duration of total sleep was 12.12 ± 2.00 hours, while that of night sleep was 9.22 ± 1.19 hours and mean daytime nap was 2.90 ± 1.66 hours. Most of the children (96%) coslept with their parents, and 55% of the children had feeding as a bedtime ritual. Overall, 19.6% of the children had sleep problems as identified by BISQ although only 5.6% of the parents perceived that their children had it. Conclusions . Sleep problems were present among young Nepalese children included in our study, and sleep assessment should be a part of every health checkup for children.